Desain Sistem Kompensasi Gaji Pokok Berbasis Person Value pada Perusahaan Agroindustri - Denni, Alex; Jamaran, Irawadi; Hermawan, Aji; Arkeman, Yandra (Jurnal Manajemen dan Organisasi, 2010)
The oobjective of this research is to design Base Pay Compensation System that based on Person Value in order to increase internal equity within a company. Person Value determined by short of competencies possessed by a job holder that relevant to the job competency model. Through this research, each and every managerial jobs under general manager completed by a competency model defined by a panel of expert. The expert panel also determines relative value of each competency based on its importance role in supporting the company achieving the goals. Person Value of job holders was calculated based on their available competency indicated through a multi-rater approach. Finally base pay of every job holders was calculated by redistributing current company budget proportionally based on their person value. The result of this research validated through a face validity method conducted by senior management team as key stake holders of the company.